FEATURES OF THE JUDICIAL PROCEDURAL SYSTEM IN NUCLEAR ENERGY - Anvarovich Ibadullaev, Timur (Antis Publisher, 2024)
The article is dedicated to studying the judicial and procedural features related to nuclear energy regulation and dispute resolution within this sector. Given the high risks associated with the operation of nuclear facilities, judicial systems must consider both national legal norms and international agreements, such as the 1963 Vienna Convention on Civil Liability for Nuclear Damage. This work analyzes the legal mechanisms of civil liability for nuclear damage and compensation procedures using examples from the United States, France, Russia, and China. Special attention is paid to the involvement of experts, procedural norms, insurance issues for nuclear operators, and appeal mechanisms. Additionally, challenges in ensuring the independence of judges in cases related to nuclear incidents and the role of international cooperation in creating unified standards for nuclear safety are explored.